Magnetic relaxation and current-voltage characteristics in a thin disk of YBa2Cu3O7-delta superconductor - Moraitakis, E.; Pissas, M.; Kallias, G.; Stamopoulos, D.; Niarchos, D. (PHYSICA B, 2000)
The relaxation of the magnetic moment of a thin disk of YBa2Cu3O7-delta superconductor in a perpendicular magnetic field shows a logarithmic dependence on time for the examined temperature range T: 10-60 K. Data are analyzed within an analytical model. The temperature dependencies of the critical current j(c), and the pinning potential U-0, are estimated by fitting the relaxation data. Furthermore, the E versus j characteristics are quantitatively derived from the relaxation data at the circumference of the disk. (C) 2000 Elsevier Science B.V. All rights reserved.